MEDIA POLITIK: SARANA PENDONGKRAK ELEKTABILITAS SEBAGAI STRATEGI PEMENANGAN PEMILU - Gusti Yasser Arafat; Nur Alfa Rahmah (UIN Antasari Banjarmasin, 2019)
Media cannot be separated from human lives, especially in digital era (IR 4.0); they aim to spread information to public and as a consequence affect public perspectives and behavior. From this point, media eventually functions to drive public opinion which in politics determine voter's choices; which in other words, media become political tools. Utilization of media for politics is significant as a winning strategy to increase electability of candidates and parties.